HF Radio Wave Diffraction on Large-Scale Disturbances of an Effective Ionospheric Boundary - Bezrodny, V. G. (Видавничий дім «Академперіодика», 2013)
HF Radio Wave Diffraction on Large-Scale Disturbances of an Effective Ionospheric Boundary